Consuming empire in US fiction, 1865-1930 - Wayne, Heather Diane (Edinburgh critical studies in Atlantic literatures and cultures., 2023)
Traces authors' attitudes toward US economic expansionism through their fictional allusions to internationally-traded commodities.